Epistemological and Axiological Integration of Legal Maxims with Maqāṣid al-Sharīʿah: Advancing Contemporary Islamic Jurisprudence - Iib Hibaturohman; Asep Risnandar; Ricky Fattamazaya Munthe (UIN Sunan Gunung Djati Bandung, 2026)
This study examines the integration of legal maxims' epistemology and axiology with maqāṣid al-sharīʿah to advance contemporary Islamic legal reform. Employing qualitative-descriptive analysis of classical texts (e.g., al-Shatibi's al-Muwafaqat, al-Ghazali's al-Mustasfa) and modern works (Jasser Auda, Ibn ʿĀshur), it highlights how maxims provide general epistemic principles from Shariah texts, while maqāṣid ensure axiological focus on benefit (jalb al-maṣlaḥah) and harm prevention (darʾ al-mafāsid). Findings reveal this synergy offers a robust basis for dynamic fiqh renewal, fostering adaptive rulings on economics, family law, technology, and environment, despite challenges like maqāṣid misuse, methodological variances, and classical limits. Ultimately, it proposes a contextual ijtihād paradigm enhancing maqāṣid-oriented uṣūl al-fiqh and equitable global policies.